Muscle reflex in heart failure: the role of exercise training - Wang, Hanjun; Zucker, Irving H.; Wang, Wei (Frontiers in Physiology, 2012)
Exercise evokes sympathetic activation and increases blood pressure and heart rate (HR). Two neural mechanisms that cause the exercise-induced increase in sympathetic discharge are central command and the exercise pressor reflex (EPR). The former suggests that a volitional signal emanating from central motor areas leads to increased sympathetic activation during exercise. The latter is a reflex originating in skeletal muscle which contributes significantly to the regulation of the cardiovascular and respiratory systems during exercise. The afferent arm of this reflex is composed of metabolically sensitive (predominantly group IV, C-fibers) and mechanically sensitive (predominately group III, A-delta fibers) afferent fibers. Activation of these receptors and their associated afferent fibers reflexively adjusts sympathetic and parasympathetic nerve activity during exercise. In heart failure, the sympathetic activation during exercise is exaggerated, which potentially increases cardiovascular risk and contributes to exercise intolerance during physical activity in chronic heart failure (CHF) patients. A therapeutic strategy for preventing or slowing the progression of the exaggerated EPR may be of benefit in CHF patients. Long-term exercise training (ExT), as a non-pharmacological treatment for CHF increases exercise capacity, reduces sympatho-excitation and improves cardiovascular function in CHF animals and patients. In this review, we will discuss the effects of ExT and the mechanisms that contribute to the exaggerated EPR in the CHF state.